2014
DOI: 10.1038/leu.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

Repression of BIM mediates survival signaling by MYC and AKT in high-risk T-cell acute lymphoblastic leukemia

Abstract: Treatment resistance in T-cell acute lymphoblastic leukemia (T-ALL) is associated with PTEN deletions and resultant PI3K-AKT pathway activation, as well as MYC overexpression, and these pathways repress mitochondrial apoptosis in established T-lymphoblasts through poorly defined mechanisms. Normal T-cell progenitors are hypersensitive to mitochondrial apoptosis, a phenotype that is dependent on expression of proapoptotic BIM. In a conditional zebrafish model, MYC downregulation induced BIM expression in T-lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…By bioinformatics analysis, we identified AKT3 as a potential target of miR-150 and this was further confirmed by a series of experiments. Based on the fact that Bim serves as a downstream target of AKT3 in T-cell acute lymphoblastic leukemia [16], and methylated AKT3 is capable of preventing its effect on the expression of Bim [25,26], we demonstrated that miR-150 negatively regulates CD4 + T cell function by targeting the AKT3/Bim pathway. Therefore, any strategies upregulating miR-150 or inactivating AKT3/Bim pathway could be used in prevention and/or treatment of aGVHD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By bioinformatics analysis, we identified AKT3 as a potential target of miR-150 and this was further confirmed by a series of experiments. Based on the fact that Bim serves as a downstream target of AKT3 in T-cell acute lymphoblastic leukemia [16], and methylated AKT3 is capable of preventing its effect on the expression of Bim [25,26], we demonstrated that miR-150 negatively regulates CD4 + T cell function by targeting the AKT3/Bim pathway. Therefore, any strategies upregulating miR-150 or inactivating AKT3/Bim pathway could be used in prevention and/or treatment of aGVHD.…”
Section: Discussionmentioning
confidence: 97%
“…Bim, a member of the BCL-2 family, is one of the key factors in AKT signaling pathway involved in the regulation of T cell apoptosis [16]. We monitored the mRNA and protein levels of Bim in CD4 + T cells when miR-150 is overexpressed.…”
Section: Mir-150 Regulates Cd4 + T Cell Function Via the Akt3/bim Patmentioning
confidence: 99%
“…[19][20][21][22][23][24]28, and 29 for reviews). The spectrum of such intracellular a-helical protein-protein interaction target space includes the BH3:Bcl-2 family, 19,[22][23][24]43,47,48,58,[67][68][69][70][71]76,77,83,92,93,98 44,45,88 Importantly, in comparison to small-molecule drug discovery, stapled peptides have shown the potential to achieve unique target family selectivity profiles that are of significant value for exploring intracellular mechanisms and/or to overcome known disease resistance mechanisms. One example of this includes the design of BID BH3, BIM BH3, BAD BH3 and Mcl-1 BH3 stapled helical peptides for Bcl-2 family targets 19,[22][23][24]43,47,58,[67][68][69][70][71]77,83,92,93,122 in which multi-specificity inclu...…”
Section: Intracellular Therapeutic Target Drug Discoverymentioning
confidence: 99%
“…[19][20][21][22][23][24][27][28][29] and 62 for reviews) for the modulation a plethora of intracellular targets (i.e. Bcl2-family, 19,[22][23][24]43,47,48,58,[67][68][69][70][71]76,77,83,92,93,98 p53:MDM2/X, 42,57,65,66,72,79,81,82,87,89,94,95 MAML:Notch, 49 eIF4E, 158 ERa/ERb, 50 IRS1, 84 HIF-1:p300, 56,90 RAS:SOS, 59 Rab-GTPase, 96 b-catenin, 64,78,80 protein kinase-A, 91 RPA, 97 HIV-1 integrase, …”
Section: Stapled Peptide Modulation Of Drug Target Spacementioning
confidence: 99%
“…Combining the analysis of a tamoxifen-regulated T-ALL model with human T-ALL cell lines, Reynolds et al identified repressed expression of BIM (a pro-apoptotic BCL2 family member) in both human and zebrafish T-ALL cells, allowing them to escape apoptosis [91]. The repressed BIM expression is mediated by MYC overexpression, as MYC downregulation upon tamoxifen removal restores bim expression in zebrafish T-ALL cells, promoting apoptosis and tumor regression in vivo.…”
Section: The Pten-pi3k-akt Pathwaymentioning
confidence: 99%